2021
DOI: 10.46786/ac21.4929
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing a Māori prison education leader

Abstract: Māori are severely over-represented in the prison population of Aotearoa New Zealand, making up over half of all prisoners, despite being only about 15% of the national population. These Māori statistics are well-known, and support racist perceptions of Māori in general. There is substantial literature on Māori imprisonment in Criminology and related fields, but it mostly focuses on ‘fixing’ the prisoner. Prison education is a neglected topic in extant educational research. Little research exists on the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…While studies have shown that delivering higher education to individuals involved with the criminal justice system reduces recidivism rates (Castro, 2018;Fullilove, Cortes, Gamarra, & Maxis, 2020;O'Brien, King, Phillips, & Kath, 2021), it has taken several decades for researchers and stakeholders to demonstrate the magnitude of this impact to governing agencies (Batiuk et al, 1997;Curtis, 2021;Evans, 2018;Nally, 2012). Even though the research is enviably clear, that higher education directly impacts recidivism, there are still several barriers that need to be addressed (Gashi, 2021;Gould, 2018;Ludlow, Armstrong, & Bartels, 2019;Te Pere & Stewart, 2021). Erzen et al, (2019) says the "lack of oversight and accountability within the prison setting, the complex needs of students, and the material scarcity that pervades the field" are common barriers that need to be addressed in higher education for incarcerated individuals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While studies have shown that delivering higher education to individuals involved with the criminal justice system reduces recidivism rates (Castro, 2018;Fullilove, Cortes, Gamarra, & Maxis, 2020;O'Brien, King, Phillips, & Kath, 2021), it has taken several decades for researchers and stakeholders to demonstrate the magnitude of this impact to governing agencies (Batiuk et al, 1997;Curtis, 2021;Evans, 2018;Nally, 2012). Even though the research is enviably clear, that higher education directly impacts recidivism, there are still several barriers that need to be addressed (Gashi, 2021;Gould, 2018;Ludlow, Armstrong, & Bartels, 2019;Te Pere & Stewart, 2021). Erzen et al, (2019) says the "lack of oversight and accountability within the prison setting, the complex needs of students, and the material scarcity that pervades the field" are common barriers that need to be addressed in higher education for incarcerated individuals.…”
Section: Literature Reviewmentioning
confidence: 99%